Type of wine and risk of lung cancer: a case-control study in Spain. Issue 11 (29th October 2004) - Ruano-Ravina, A; Figueiras, A; Barros-Dios, J M
Abstract : Background: Few epidemiological studies have examined the effect of wine on the risk of lung cancer. A study was therefore undertaken to estimate the effect of wine consumption, both overall and by type of wine, on the risk of developing lung cancer. Methods: A hospital based case-control study was conducted on 319 subjects (132 cases, 187 controls) in 1999–2000. All subjects were interviewed about their lifestyles with particular reference to alcohol consumption and tobacco use. The results were analysed using non-parametric logistic regression. The main outcome measure was the risk of lung cancer associated with consumption of wine and its individual types. Results: A very slight but significant association was observed between the risk of lung cancer and white wine consumption (odds ratio (OR) 1.20 for each daily glass). Red wine consumption, on the other hand, had an OR of 0.43 (95% CI 0.19 to 0.96), with each daily glass of red wine having an inverse association with the development of lung cancer (OR 0.87 (95% CI 0.77 to 0.99)). There was no apparent association between lung cancer and consumption of beer or spirits. Conclusions: These results suggest that the consumption of red wine is negatively associated with the development of lung cancer. Further studies are needed to test this finding in cancer induced laboratory animals.